Optical Properties of DMA-π-DCV Derivatives: A Theoretical Inspection under the DFT Microscope - Joaquín Calbo (Journal of Spectroscopy)
The optical properties of a series of donor-acceptor N,N-dimethylaniline-π-dicyanovinylene (DMA-π-DCV) chromophores have been investigated under the density functional theory framework. Focus has been made on the low-lying charge-transfer (CT) electronic transitions for which experimental data is available. The effect of the π-conjugated bridge length and type was analysed between the families of oligoene and oligoyne derivatives of increasing size. Theoretical calculations demonstrate that the ethylene bridge is a better π-communicator and allows for more delocalized frontier molecular orbitals compared to the acetylene spacer. The Λ diagnostic test allowed rationalization of the orbital spatial overlap in the main CT excitations. The performance of different density functional rungs was assessed in the prediction of the lowest-lying CT electronic transition. Surprisingly, most modern long-range corrected functionals demonstrated to provide among the largest errors, whereas hybrid functionals showed the best performance. Solvatochromism was confirmed in both oligoene and oligoyne compounds. A donor-acceptor-donor triad based on tetrathiafulvalene was utilised as a test system for the prediction of its two CT bands of different nature, energy, and intensity. The hybrid PBE0 (or a similar hybrid analogue) consolidates as the best choice for the prediction of CT excitations in the DMA-π-DCV push-pull family.